Pengaruh Literasi Kewirausahaan dan Literasi Ekonomi Terhadap Motivasi Berwirausaha Siswa di SMA Negeri 8 Palembang - Retno Anggrayni; Neta Dian Lestari; Januardi Januardi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Based on the results of observations made by researchers, that students' knowledge of entrepreneurial literacy and economic literacy is quite good. This study aims to determine the effect of entrepreneurial literacy and economic literacy on entrepreneurial motivation. This study uses a quantitative method with a correlational approach. The research population was 98 students of SMA Negeri 8 Palembang for the academic year 2023/2024 even semester, the sample was determined using the Census/Sampling method. The total number was 98 people. Entrepreneurial literacy and economic literacy data were collected through multiple choice test questions and data on entrepreneurial motivation was carried out through a questionnaire. Based on the results of hypothesis testing, it shows that entrepreneurial literacy and economic literacy have a simultaneous effect on entrepreneurial motivation assisted by SPSS software with a sig. 0.000 is less than 0.05 (0.000 <0.05) and the Fcount value is 434.700 greater than Ftable = 3.09 (at the 5% tolerance level and degrees of freedom (df) (k; n-k) = (2;96), Entrepreneurial literacy partially influences entrepreneurial motivation with a sig. value of 0.000 less than 0.05 (0.000 <0.05), and a tcount of 9.377 greater than a ttable of 1.985 (at the 5% tolerance level and degrees of freedom (df) n - 2 = 95) and economic literacy partially influences entrepreneurial motivation with a significance value (sig.) 0.000 less than 0.05 (0.000 <0.005) and a tcount value of 9.834 more than ttable 1.985 (at the 5% tolerance level and degrees of freedom (df) n-2=95).Â Keywords: Entrepreneurial Literacy; economic literacy; entrepreneurial motivation.Â